Antibacterial activity of combined ethanolic extracts of a. Bilimbi, o. Stamineus, m. Nigra, p. Granatum, and e. Longifolia against acne-causing bacteria - Mahmood Hasan, Mahmood Al Doori (2024)
Plant resources have been used as traditional medicines and alternative therapies for centuries. The high cost and huge side effects of chemical treatments were the main reasons behind the utilisation of plant-based products for medical related issues. In this study, five plants (A. bilimbi, O. stamineus, M. nigra, P. granatum, and E. longifolia) were selected and studied as potential sources of alternative therapeutic agents against acne-causing bacteria (S. aureus, C. acnes, and S. epidermidis) in humans. The plants were extracted using ultrasonic extraction techniques and the phytochemical contents of the extracts were determined using several biochemical tests and GC-MS. Through the preliminary antibacterial screening by disc diffusion, P. granatum and O. stamineus were identified as the two most potent extracts and were combined in the ratio of 1:1, 1:2, and 2:1 at a total concentration of 400 mg/Ml for more investigations on their combined efficacy against the studied microbes. For antioxidant assays, DPPH, ABTS and FRAP assays were applied to evaluate the antioxidant properties. P. granatum and O. stamineus were selected for combination based on their IC50 values of 83.4% for DPPH and 83.24% for ABTS at a 1:1 ratio. The antibacterial efficacy of the mixtures was studied via disc diffusion and the MIC value was determined. Both S. aureus and S. epidermidis were sensitive to all the individual and combined extracts, but C. acnes was resistant to all the extracts except P. granatum which had little effect on the growth of the microbe. The antibacterial activity of the combined extracts against S. aureus showed synergistic effect at the ratio of 2:1 with the inhibitory zone of 18.00 ± 1.00 mm and MIC value of 12.5 mg/mL but showed antagonistic effects against S. epidermidis and no activity towards C. acnes. In general, this research demonstrated that combining two plant extracts with relatively low biological activities at different combination ratios can significantly improve the biological response to certain human diseases.